Evaluation of Right Ventricular Myocardial Mechanics by 2- and 3-Dimensional Speckle-Tracking Echocardiography in Patients With an Ischemic or Non-ischemic Etiology of End-Stage Heart Failure - Tian, Fangyan; Gu, Ying; Zhang, Yanting; Zhang, Bei; Xie, Yuji; Yu, Shaomei; Zhu, Shuangshuang; Sun, Wei; Cheng, Shan; Qian, Mingzu; Lin, Yixia; Wu, Wenqian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The aims of our study were (1) to assess the right ventricular (RV) myocardial mechanics by two-dimensional (2D) and three-dimensional (3D) speckle-tracking echocardiography (STE) in patients with an ischemic or non-ischemic etiology of end-stage heart failure (HF) and (2) to explore which RV index evaluated by 2D- and 3D-STE was the most powerful indicator for identifying the ischemic and non-ischemic etiologies of end-stage HF. Methods: Ninety-six patients with left ventricular ejection fraction (LVEF) < 30% were enrolled in our study: forty-two patients (mean age, 52±10 years; 9.5% female) with ischemic cardiomyopathy and fifty-four patients (mean age, 46±14 years; 16.7% female) with non-ischemic cardiomyopathy. Forty-five healthy (mean age, 46±13 years; 24.4% female) subjects served as controls. The longitudinal strain of the RV free wall (RVFWLS) was determined by both 2D- and 3D-STE. Results: Compared to controls, patients with an ischemic or non-ischemic etiology of end-stage HF had higher RV end-diastolic volume index (RVEDVI) and RV end-systolic volume index (RVESVI) , and lower 2D-RVFWLS, 3D-RVFWLS and RV ejection fraction (RVEF) values (P < 0.05). Patients with non-ischemic cardiomyopathies (NICMs) had significantly lower 3D-RVFWLS and RVEF values than in those with ischemic cardiomyopathies (ICMs), whereas 2D-RVFWLS and conventional RV function parameters did not differ between the two subgroups. RVEF was highly related to 3D-RVFWLS (r = 0.72, P < 0.001), modestly related to 2D-RVFWLS (r = 0.51, P < 0.001), and weakly related to conventional RV function indices (r = -0.26¬–0.46, P < 0.05). Receiver operating characteristic curve analysis revealed that the optimal 3D-RVFWLS cut-off value to distinguish NICM from ICM patients was -14.78% (area under the curve: 0.73, P < 0.001), while 2D-RVFWLS and conventional RV echocardiographic parameters did not. Conclusions: Our study demonstrated the superiority of 3D-RVFWLS over 2D-RVFWLS and conventional RV function indices in identifying the ischemic and non-ischemic etiologies of end-stage HF. These findings support the idea that 3D-RVFWLS may be a promising non-invasive imaging marker for distinguishing NICM from ICM.